Analisis Metode Economic Order Quantity, Safety Stock, Reorder Point, dan Cost of Inventory dalam Mengoptimalkan Manajemen Persediaan Umkm Bakso Pedas - Niswah Itsna R; Intan Nirwana A; Revita Widya P; Mohamad Bastomi (PT FORMOSA CENDEKIA GLOBAL, 2023)
When running a business, management is an important thing to be carried out by all UMKM actors. UMKM Spicy Meatballs is a business engaged in the culinary or food sector. The purpose of this study was to determine the application of merchandise inventory management and to find out the efforts made in anticipating merchandise losses at Unisma's Spicy Meatballs. The type of research used is field research using a qualitative approach and as a source of information in this research is the seller of Spicy Meatballs beside the unisma campus where it is in the food court. During the research, a qualitative method was applied by conducting direct interviews with the owner of Spicy Meatballs to obtain the data used in calculating inventory. Therefore, this study tries to calculate ordering costs and storage costs for Spicy Meatballs using the EOQ method, in order to assist owners in managing their inventory. The results of the Spicy Meatball UMKM research show that the EOQ method can help Spicy Meatball UMKM in minimizing the cost of ordering supplies. The EOQ method also helps owners find out the optimal number and frequency of orders